2012
DOI: 10.1111/j.1365-3180.2012.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two patch spraying systems in winter wheat and maize

Abstract: Gutjahr C, Sökefeld M & Gerhards R (2012). Evaluation of two patch spraying systems in winter wheat and maize. Weed Research52, 510–519. Summary Fifteen field experiments were conducted in winter wheat and maize to analyse the spatial distribution of weed species and to evaluate two systems of site‐specific weed control. Fields were divided into cells and weed densities for all weed species were counted in each cell. Weed species were then grouped into annual broad‐leaved species, grass weeds and Galium aparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…For example, Häusler et al (1998) found that herbicide applications in two winter wheat fields were necessary for 24% and 35% of the area against G. aparine L., for 25% and 31% of the area against other dicotyledonous weeds, and for 55% and 7.5% of the area against grasses. Gutjahr et al (2012) calculated herbicide savings in 11 winter wheat fields treated with SSWM. Average untreated area was 70% for broad-leaved species and 59% for grass weeds.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Häusler et al (1998) found that herbicide applications in two winter wheat fields were necessary for 24% and 35% of the area against G. aparine L., for 25% and 31% of the area against other dicotyledonous weeds, and for 55% and 7.5% of the area against grasses. Gutjahr et al (2012) calculated herbicide savings in 11 winter wheat fields treated with SSWM. Average untreated area was 70% for broad-leaved species and 59% for grass weeds.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in the case of chemical tools, various works have already demonstrated the technical feasibility of precision weed control implements. Numerous works addressed the use of chemical sprayer able to turn on or off boom sections or individual nozzles [4][5][6][7][8] to applied herbicides specifically on clusters or individual weed plants. Concerning physical weed management, technologies had also been developed to guide weeding devices according to weed detection in fields [9].…”
Section: Introductionmentioning
confidence: 99%
“…The species mostly occur in spring crops such as maize, sugar beet and sunflower, but also infest cereal crops, vineyards and orchards (Mehrtens et al 2005, Pfirter et al 1997, Parsons & Cuthbertson 2001. Due to their predominant vegetative propagation they often grow in aggregated patches (Gutjahr et al 2012) and tend to increase in abundance in the absence of tillage (Streit et al 2002, Rusu et al 2006, Knezevic et al 2008. The bindweeds from the family of Convolvulaceae are in direct competition with the crop by their climbing habit due to physico-mechanical stimuli (Kleinsteuber et al 1996).…”
Section: Introductionmentioning
confidence: 99%